Find Hire Freelancers (FHF) mobile app - Syed Hasbie, Sharifah Nur Hafizah; Ismail, Ismariani (2024)
Find Hire Freelancers (FHF) is a mobile application that is used to provide multiple types of services to customers in Kuching, Sarawak. The problems occurring from the current situation is the customers having too many choices that makes decision-making more challenging. The customers also need to spend an excessive amount of time sorting through numerous listings, uncertain about which ones suit them. Besides that, the existing gig worker apps rely on a directory-based structure, limiting user engagement and efficiency. The FHF Mobile App was proposed to overcome the problems. The first objective of FHF is to have an application that eases the user to choose a service. This will prevent the paradox of choices from occurs. Second objective is to create a user-friendly interface that can facilitate the connection between skilled vendors and clients seeking their services. This will shorten the time to survey on suitable vendors. The third objective is to develop a mobile application that can preset the charges applied to each service. The software needed to develop FHF include Flutter, Visual Studio Code, and Android Studio. As a result, these mobile apps achieved the objective as the customers can save their time of choosing a vendor. These apps assigned the vendors and the actual price of services. The FHF has determined much potential to be used as the center of freelancers to provide their services in Kuching, Sarawak.